The Analysis of Government's Policy to Enhance The Student's Religious Commitment: Analytical Study on Public Senior High School's Students of Blitar Town - Syahidah, Nila Lukmatus (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
Generally politics and education have their own roles and have no relation, or probably weak relation. Finding a phenomenon that in Blitar Town there is a policy relating education interests the research to know more about the policy, the background, the implementation, and relate the policy implementation to the students religious commitment developments, which consists of five aspects, they are knowledge, belief, practice, experience, and consequence. This study is undertaken by collecting data from the government, the regional education official, the LPTQ, PAI teacher of pubic senior high schools of Blitar Town, and the students, by using interview, observation, and documentation. There are four public senior high schools of BlitarTown, they are SMAN 1 Kota Blitar, SMAN 2 Kota Blitar, SMAN 3 Kota Blitar, and SMAN 4 Kota Blitar. The study is focused only on public schools because the systems of schools are administrated by the government. The result of the study shows that the implementation of the policy give contribution to the students’ religious commitment, whether every students get different feeling, development or increasing of their religious life after they join and pass the competence test.